Studi Etnobotani Suku Tajio Di Desa Sienjo Kecamatan Toribulu Kabupaten Parigi Moutong Sulawesi Tengah - Yuliarsih Yuliarsih; Eny Yuniati; Ramadhanil Ramadhanil (Biocelebes, 2013)
The research entitled “Ethnobotanical study of Tajio Tribe at Sienjo Village, Toribulu District, Parigi Moutong Regency Central Sulawesi has been done from November 2012-Ferbuari 2013. The research aimed were to know the diversity of useful plants, part of plant, and how to prepare its plant which were used by them. The research noethod was exploration survey by using Participary Rural Appraisal (PRA). The results of the research showed that there were 114 plants spesies which were used by Tajio tribe indaily activities.The plants species were utilized for different purpose such as food stuff (46 species), medicinal (36 species), ritual (18 species), ornamentals (15 species), dyes (3 species), contructions (8 species), spices (13 species), and as animal food (5 species). Keywords:Ethnobotany, Useful plants, Tajio ethnic, Village Sienjo, ICS